The Effect of Progressive Movement in Saraiki ’Nazm’ - Perveen, Fauzia; Saleem, Muhammad (sourcecoder, 2022)
The Saraiki language is one of the ancient languages of the Indus valley that is why it has a great wealth of literature. Literature reflects the development of any language and the civilization and culture of the region. When we seek progressiveness in Saraiki literature we can aboserve its effects after the establishment of Pakistan. The sufis of this region promoted progressive thinking and enlightenment along with the spread of Islam. They vehemently criticized the attitudes of kings and feudal lords and always speaking for common man. This is the reason why progressive trends are evident in Saraiki poetry. Like others languages of the world, Saraiki language and its poetry have evolved over time, adapting to changes in its form and temperament. The Saraiki conference held in Multan in 1975 which proved significiant for the formation of modern Saraiki poetry. Irshad Tounsvi, Abid Ameeq, Hassan Raza Gardaizi, Aslam Javaid, Iqbal Sokri and Nasrullah Khan Nasir are the representative poets of the modern Saraiki poetry. This article sum up the influence of the progressive movement in modern Saraiki “Nazm”.